Esprit civique et organisation citadine dans l'Empire ottoman. - Nora Lafi (The Ottoman Empire and its Heritage, 2019)
This book proposes a study of the old regime forms of Ottoman municipal urban governance that were progressively built between the 15th and the 18th c. on the basis of various heritages (Byzantine, Medieval Islamic, Seljukid, Sassanid, medieval Ottoman) as well as an interpretation of the reforms of the Tanzimat era under the light of this re-evaluation of the previous system. This allows the author to propose innovative ideas on the very nature of civic life, social organization and modernity in the Islamic world. The research is based on original archives from Istanbul (BOA) and various cities of the Empire, from Aleppo to Tunis, Thessaloniki to Alexandria or Damascus and Cairo to Tripoli. Cet ouvrage est consacré à l'étude des racines et des caractéristiques de la gouvernance urbaine dans l'empire ottoman. Il démontre comment s'est développée sur la base de différents héritages (Byzantin, Islamique médiéval, Seljukide, Sassanide et Ottoman médiéval) à partir du XVe siècle une forme municipale d'ancien régime et étudie sa transformation durant les réformes de l'ère des Tanzimat au XIXe siècle. L'auteure propose ainsi des interprétations innovantes quant à la dimension civique de la vie urbaine, l'organisation sociale et l'impact ambigu avec la modernité dans un contexte islamique. L'étude s'appuie sur des archives inédites trouvées à Istanbul (BOA) et dans des villes comme Alep, Tunis, Thessalonique, Alexandrie, Damas, Le Caire et Tripoli